High-spatial-resolution probability maps of drought duration and magnitude across Spain - F. Domínguez-Castro; S. M. Vicente-Serrano; M. Tomás-Burguera; M. Peña-Gallardo; S. Beguería; A. El Kenawy; A. El Kenawy; A. El Kenawy; Y. Luna; A. Morata (Natural Hazards and Earth System Sciences, 2019)
Assessing the probability of occurrence of drought is important for improving current drought assessment, management and mitigation measures, and strategies across Spain. This study employed two well-established drought indices, the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI), to characterize drought duration and magnitude at different timescales over Spain. In order to map the drought hazard probability, we applied the extreme value theory and tested different thresholds to generate peak-over-threshold (POT) drought duration and magnitude series. Our results demonstrate that the generalized Pareto (GP) distribution performs well in estimating the frequencies of drought magnitude and duration. Specifically, we found a good agreement between the observed and modelled data when using upper percentiles to generate the POT series. Spatially, our estimations suggest a higher probability of extreme drought events in southern and central Spain compared to the northern and eastern regions. Also, our study found spatial differences in drought probability estimations as a function of the selected drought index (i.e. SPI vs. SPEI) and timescale (i.e. 1, 3, 6, and 12 months). Drought hazard probability maps can contribute to the better management of different sectors (e.g. agriculture, water resources management, urban water supply, and tourism) at national, regional, and even local scale in Spain.